The factors influencing public intention to use Islamic personal loan / Salwani Ismail - Ismail, Salwani (2012)
For this study, the researcher aim to examine the factors that influence public intention to use the Islamic personal loan at the bank in Kelantan that offers Islamic personal loan. There are three factors being studied, which were: attitude, social influence and pricing. About 100 of questionnaires were distributed by hand to the government and private employees from Kelantan area. The research findings show that the most factors influenced the intention to use of Islamic personal loan was social influenced. The respondents were strongly agree that the influence from family members and friends affected consumer to choose Islamic personal loan. However, the findings show that another two variables were not significant with the intention to use Islamic personal loan. As a conclusion, the results of the findings that include the analysis of the demographic profile and the most factors influence the intention to use Islamic personal loan. For the recommendation of this study made based on several logical factors and impact of current situation to the intention of the public towards the Islamic personal loan